2012
DOI: 10.1177/000348941212101109
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Distinction of Unique Vocal Fold Subepithelial Architectures Using Optical Coherence Tomography

Abstract: Optical coherence tomography was developed for in vivo imaging of biological microstructures. This study demonstrates the ability of OCT to differentiate between the vocal fold architectures of 3 histologically distinct types of vocal folds. Future studies aim to develop a quantitative optical imaging algorithm that can be used to facilitate an in vivo longitudinal clinical investigation of the changes that occur in this layered structure over time and maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Maturo et al performed ex vivo OCT imaging on cadaveric adult pig as well as fetal and adult human specimens. Graphical analysis of image intensity as a function of image depth revealed unique image intensity profiles for each specimen type suggesting the observed differences may be attributable to differences in lamina propria substructure . Again, this study was limited by a small sample size, so we developed an OCT probe suitable for in vivo vocal fold imaging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturo et al performed ex vivo OCT imaging on cadaveric adult pig as well as fetal and adult human specimens. Graphical analysis of image intensity as a function of image depth revealed unique image intensity profiles for each specimen type suggesting the observed differences may be attributable to differences in lamina propria substructure . Again, this study was limited by a small sample size, so we developed an OCT probe suitable for in vivo vocal fold imaging .…”
Section: Introductionmentioning
confidence: 99%
“…Graphical analysis of image intensity as a function of image depth revealed unique image intensity profiles for each specimen type suggesting the observed differences may be attributable to differences in lamina propria substructure. 20 Again, this study was limited by a small sample size, so we developed an OCT probe suitable for in vivo vocal fold imaging. 21 We set out to image young and old pediatric patients to see if unique image intensity profiles could be captured.…”
Section: Introductionmentioning
confidence: 99%
“…We are focusing on optical coherence tomography (OCT) of the swallowing process in the oesophagus and larynx as well as on the vocal fold function (18Á20). It can be shown on OCT how the layers of the vocal folds develop, possibly corresponding to hormonal and paediatric development (21,22). The arytenoid area in the larynx should be focused upon with OCT in pathology.…”
Section: Discussionmentioning
confidence: 99%
“…35 Maturo and colleagues 36 showed that OCT may be used to quantitatively analyze the layers of the lamina propria of the vocal fold. This feature of OCT has the potential to help to characterize the subepithelial development of the pediatric vocal fold and help determine the need for operative intervention in children with dysphonia.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%